2019
DOI: 10.1016/j.euf.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Penile Squamous Cell Carcinoma Patients Undergoing Inguinal Lymph Node Dissection

Abstract: Penile cancer is a rare malignancy in North America and Europe. Therefore, there is a lack of prognostic parameters to help predict oncologic and survival outcomes. In this report, patients with an elevated neutrophil-to-lymphocyte ratio had an increased risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 26 publications
1
36
2
Order By: Relevance
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had signi cantly worse CSS [17,18] and OS [16];Patients with a low LMR had signi cantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had signi cantly worse CSS [17,18] and OS [16];Patients with a low LMR had signi cantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had significantly worse CSS [17,18] and OS [16];Patients with a low LMR had significantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…In logistic regression analyses, NLR (HR = 2.212; 95% CI: 1.228-3.985,p = 0.008), LMR(HR = 0.537; 95% CI: 0.308-0.937,p = 0.029), PLR(HR = 2.478; 95% CI:1.365-4.497,p = 0.003) was significant Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had significantly worse CSS [17,18] and OS [16];Patients with a low LMR had significantly worse RFS and CSS than those with a high…”
Section: Nlr Lmr Plr Ldh Vs Inguinal Lymph Node-negative/positivementioning
confidence: 99%
“…Recently it has been reported that cancer patients with high NLR is associated with worse OS [16]and worse RFS and CSS [17,18]. However, there has been no study evaluating the PLR associated with outcomes of penile cancer.…”
mentioning
confidence: 99%